2022
DOI: 10.1002/pon.5945
|View full text |Cite
|
Sign up to set email alerts
|

Prodromal depression and anxiety are associated with worse treatment compliance and survival among patients with pancreatic cancer

Abstract: Objective To determine the frequency of depression or anxiety preceding a diagnosis of pancreatic cancer (PC). Further, to examine the association of PC‐associated depression or anxiety with treatment compliance and survival. Methods 856 patients with PC from a single institution were identified using International Classification of Diseases (ICD) codes. For each case, two non‐cancer age‐ and sex‐matched controls were included. Dates of depression or anxiety diagnosis identified using ICD codes were compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 54 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…Besides, the psychological burden negatively The survival curves based on waiting time within one month for overall survival (A) and cancer-specific survival (B), or waiting time within two months for overall survival (C) and cancer-specific survival (D). influenced survival quality and prognosis in patients with malignant tumors (27,28). Our findings showed that the waiting time ≥3 months had a significant negative effect on CSS and OS for stage IA1 NSCLC patients after adjusting for other confounders, and the waiting time ≥2 months only influenced OS rates.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Besides, the psychological burden negatively The survival curves based on waiting time within one month for overall survival (A) and cancer-specific survival (B), or waiting time within two months for overall survival (C) and cancer-specific survival (D). influenced survival quality and prognosis in patients with malignant tumors (27,28). Our findings showed that the waiting time ≥3 months had a significant negative effect on CSS and OS for stage IA1 NSCLC patients after adjusting for other confounders, and the waiting time ≥2 months only influenced OS rates.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies confirmed that greater psychological distress was associated with slower time to treatment in oncological patients ( 25 , 26 ). Besides, the psychological burden negatively influenced survival quality and prognosis in patients with malignant tumors ( 27 , 28 ). Our findings showed that the waiting time ≥3 months had a significant negative effect on CSS and OS for stage IA1 NSCLC patients after adjusting for other confounders, and the waiting time ≥2 months only influenced OS rates.…”
Section: Discussionmentioning
confidence: 99%
“…9,31 The prevalence of patient depression and anxiety was associated with nonreceipt of chemotherapy treatment and poorer overall survival. 32 It is likely that patients' caregivers also experience similar impairment to their well-being in the preoperative setting. Future studies should include caregiver assessment at the time of preoperative evaluation as another important time to provide initial support.…”
Section: Discussionmentioning
confidence: 99%
“…A PHQ-9 total score ≥5 indicated MDD, while a GAD-7 total score ≥5 indicated anxiety. The severity of MDD was graded as Grade I (5-9), Grade II (10)(11)(12)(13)(14), Grade III (15)(16)(17)(18)(19), and Grade IV (20)(21)(22)(23)(24)(25)(26)(27). Anxiety severity was graded as Grade I (5-9), Grade II (10)(11)(12)(13)(14), and Grade III (15)(16)(17)(18)(19)(20)(21).…”
Section: Questionnaire Of Mental Assessments and Quality Of Lifementioning
confidence: 99%